1973
DOI: 10.1113/jphysiol.1973.sp010089
|View full text |Cite
|
Sign up to set email alerts
|

Sensory inputs to neurones in Clarke's column from muscle, cutaneous and joint receptors

Abstract: SUMMARY1. Discharge of neurones at the region of Clarke's column of the cat was recorded intracellularly or extracellularly in response to electrical stimulation of various hind limb nerves or to adequate stimuli applied to a variety of sensory receptors.2. According to the type of excitatory sensory input, the neurones were classified into four groups. Their relative proportions were: muscle group, 55-65 %; cutaneous group, 15-25 %; joint group, 5-15 %; convergent group, 10-20%.3. The location of the neurone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This appears to be in contrast to monosynaptic excitation from group I fibres of Clarke's column neurones, the majority of which have been considered to be activated primarily from a single muscle or a few synergists (Holmqvist, Lundberg & Oscarsson, 1956;Eccles, et al 1961 b;Mann, 1971;Kuno et al 1973; Knox et al 1977); Mann (1971) and Knox et al (1977) reported convergence of monosynaptic actions from more than one muscle or muscle group in about 20 % of DSCT axons, but the sampled axons in these studies could originate not only from Clarke's column but also from more caudal levels. For comparing the degree of convergence in the caudal spinocerebellar neurones now under study with that in Clarke's column neurones, only some of the previously reported observations can be used, because some studies used only intra-252 SENSORY INPUT TO NON-CLARKE DSCT CELLS axonal recording from DSCT fibres which discloses only supraliminal effect (Holmqvist et al 1956) and other studies used a much smaller number of peripheral nerves for testing (Kuno et al 1973;Knox et al 1977). In the intracellular study of Clarke's column neurones by Eccles et al (1961 b) in which various nerves of the hindlimb were extensively tested, convergence of afferents from different mascles was found in 36 % (twenty-one out of fifty-eight) of neurones.…”
Section: Effects From the Framentioning
confidence: 64%
See 3 more Smart Citations
“…This appears to be in contrast to monosynaptic excitation from group I fibres of Clarke's column neurones, the majority of which have been considered to be activated primarily from a single muscle or a few synergists (Holmqvist, Lundberg & Oscarsson, 1956;Eccles, et al 1961 b;Mann, 1971;Kuno et al 1973; Knox et al 1977); Mann (1971) and Knox et al (1977) reported convergence of monosynaptic actions from more than one muscle or muscle group in about 20 % of DSCT axons, but the sampled axons in these studies could originate not only from Clarke's column but also from more caudal levels. For comparing the degree of convergence in the caudal spinocerebellar neurones now under study with that in Clarke's column neurones, only some of the previously reported observations can be used, because some studies used only intra-252 SENSORY INPUT TO NON-CLARKE DSCT CELLS axonal recording from DSCT fibres which discloses only supraliminal effect (Holmqvist et al 1956) and other studies used a much smaller number of peripheral nerves for testing (Kuno et al 1973;Knox et al 1977). In the intracellular study of Clarke's column neurones by Eccles et al (1961 b) in which various nerves of the hindlimb were extensively tested, convergence of afferents from different mascles was found in 36 % (twenty-one out of fifty-eight) of neurones.…”
Section: Effects From the Framentioning
confidence: 64%
“…The same holds true for the neurones with cutaneous input. Clarke's column neurones were reported to respond to stimulation of only one cutaneous nerve (Kuno et al 1973), while 38 % of the present spinocerebellar neurones with skin input were excited by cutaneous afferents from two or three nerves.…”
Section: Effects From the Framentioning
confidence: 67%
See 2 more Smart Citations
“…The spontaneous firing rate of DSCT neurons as a population decreases during AS relative to W and QS. This difference may be attributable in part to the different types of afferent information conveyed by TGT (Sessle and Greenwood, 1976;Azerad et al, 1982;Sessle et al, 1986;Ro and Capra, 1994) as opposed to DSCT neurons (Kuno et al, 1973;Mann, 1973;Walmsley, 1991) and/or different central regulatory mechanisms (Cairns et al, , 1996Soja et al, 1996a).…”
Section: State-dependent Changes In Ongoing Spike Dischargementioning
confidence: 99%